The Use of English Language Learning Strategies in learning as Foreign Language (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The purpose of this quantitative descriptive study is to identify the English language learning strategies employed by university students in North Sulawesi.  It also explains the ways in which male and female students approach learning English differently, as well as the kinds of strategies that they most frequently employ.  The survey included 91 students enrolled in a Business English course during the second semester of 2020/2021.  The SILL questionnaire, with 50 items over six categories, namely, cognitive, metacognitive, affective, memory, and social strategies, was the instrument utilized in this investigation.  The findings indicate that when learning English, students in Business English classes mostly employ Cognitive, Compensatory, and Metacognitive strategies.  Based on gender, male students tended to employ cognitive strategies, while female students tended to use metacognitive strategies.  This study is significant for the English teachers, students, and the school to inform them about the learning strategies that they usually use in learning English.
Keywords: English; Foreign Language; Language Learning Strategies